Transformasi Digital UMKM: Strategi Pemasaran di Era Globalisasi - Muh. Syata, Wahyu (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This research examines the role of digital transformation thru social media marketing strategies in improving the performance and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia in the era of globalization. The research method uses a qualitative approach with a literature review of relevant literature from national and international journals, books, and scientific articles. The research findings indicate that the adoption of digital technology, particularly social media platforms such as Facebook, Instagram, TikTok, and WhatsApp, has proven to enhance operational efficiency, productivity, product visibility, and market reach for MSMEs, with lower promotional costs compared to conventional methods. The success of digital transformation is influenced by several key factors, including technology infrastructure, organizational readiness, environmental awareness, human resource digital literacy, and government policy support. Social media not only serves as a promotional tool but also as a strategic information source thru the analysis of consumer behavior data and market trends, supporting accurate and responsive business decision-making. The challenges faced by MSMEs include limited digital literacy, a shortage of skilled human resources, and suboptimal data analysis capabilities. Digital transformation has a multidimensional impact on MSMEs, strengthening marketing aspects, increasing operational efficiency, driving product innovation, and enhancing competitiveness and business sustainability in the context of globalization. Collaborative efforts between the government, the private sector, and academia are needed to strengthen the digital ecosystem and sustainably enhance the human resource capacity of MSMEs